Back Dominant Pain Has Equal Outcomes to Radicular Dominant Pain Following Posterior Lumbar Fusion in Adult Isthmic Spondylolisthesis: A CSORN Study. Issue 8 (October 2022) - Alnaghmoosh, Nabeel; Urquhart, Jennifer; Raj, Ruheksh; Abraham, Edward; Jacobs, Bradley; Phan, Philippe; Johnson, Michael; Paquet, Jerome; Nataraj, Andrew; McIntosh, Greg; Fisher, Charles G.; Rampersaud, Y. Raja; et al.
Study Design: Retrospective Cohort Study. Objectives: This study aimed to determine how the surgeon-determined and patient-rated location of predominant pain influences patient-rated outcomes at 1-year after posterior lumbar fusion in adult isthmic spondylolisthesis. Methods: We retrospectively reviewed consecutive patients prospectively enrolled in the Canadian Spine Outcomes and Research Network national registry between 2009 and 2017 that underwent posterior lumbar fusion for isthmic spondylolisthesis. Using longitudinal mixed-model repeated-measures analysis the change from baseline in patient-reported outcome measures (PROMs) at 1 year after surgery was compared between surgeon-determined groups (back vs. radicular) and between patient-rated pain groups (back, leg, and equal) derived from preoperative pain scores on the numerical rating scale (NRS). Results: 83/252 (33%) patients had a surgeon-determined chief complaint of back pain, while 103 (41%) patients rated their back pain as the predominant pain location, and 78 (31%) rated their back and leg pain to be equal. At baseline patients in the surgeon-determined radicular group had worse NRS-leg pain than those in the back-pain group but equal NRS-back pain. At baseline patients in the patient-rated equal pain group had similar back pain compared to the patient-rated back pain group and similar leg pain compared to the patient-rated leg pain group. All PROMs improved post-operatively and were not different between the 2 groups at 1 year. Conclusions: Our study found no difference in outcome, irrespective of whether a surgeon determines the patient's primary pain complaint back or radicular dominant, or the patient rates pain in one location greater than another.